2017
DOI: 10.3892/ol.2017.5954
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Duffy antigen receptor for chemokines by epithelial ovarian cancer decreases growth potential

Abstract: Epithelial ovarian cancer (EOC) is one of the main causes of cancer-associated mortality in females with gynecological malignancies. Duffy antigen receptor for chemokines (DARC) has previously been reported to be involved in tumor growth and the inhibition of tumor metastasis. However, the association between DARC and EOC remains unknown. The aim of the present study was to investigate the expression of DARC in the SKOV3 human epithelial ovarian cancer cell line with the establishment of a subcutaneous model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Indeed, ACKR1 was strongly connected to improved outcomes in breast cancer as well as in several other malignancies, at times upon co-expression with ACKR2 or ACKR4 (188)(189)(190)(191)(192). Accordingly, ACKR1 was causatively linked to reduced tumor growth and metastasis in animal models, and ACKR1 single nucleotide polymorphisms that were related to chemokine sequestration affected angiogenesis, tumorigenesis and lung metastasis (193)(194)(195). The anti-tumor activities of ACKR1 were mediated not only by reducing microvessel density, but also by inhibiting atypical cancer-related activities, such as MMP9 production and tumor cell proliferation, as well as increasing tumor cell senescence (192,(194)(195)(196); from the mechanistic perspective, it was demonstrated that ACKR1 caused anti-tumor effects by interfering with CXCR2-induced STAT3 activation in pancreatic adenocarcinoma cells (192).…”
Section: Activities Of Atypical Chemokine Receptors In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ACKR1 was strongly connected to improved outcomes in breast cancer as well as in several other malignancies, at times upon co-expression with ACKR2 or ACKR4 (188)(189)(190)(191)(192). Accordingly, ACKR1 was causatively linked to reduced tumor growth and metastasis in animal models, and ACKR1 single nucleotide polymorphisms that were related to chemokine sequestration affected angiogenesis, tumorigenesis and lung metastasis (193)(194)(195). The anti-tumor activities of ACKR1 were mediated not only by reducing microvessel density, but also by inhibiting atypical cancer-related activities, such as MMP9 production and tumor cell proliferation, as well as increasing tumor cell senescence (192,(194)(195)(196); from the mechanistic perspective, it was demonstrated that ACKR1 caused anti-tumor effects by interfering with CXCR2-induced STAT3 activation in pancreatic adenocarcinoma cells (192).…”
Section: Activities Of Atypical Chemokine Receptors In Cancermentioning
confidence: 99%
“…Accordingly, ACKR1 was causatively linked to reduced tumor growth and metastasis in animal models, and ACKR1 single nucleotide polymorphisms that were related to chemokine sequestration affected angiogenesis, tumorigenesis and lung metastasis (193)(194)(195). The anti-tumor activities of ACKR1 were mediated not only by reducing microvessel density, but also by inhibiting atypical cancer-related activities, such as MMP9 production and tumor cell proliferation, as well as increasing tumor cell senescence (192,(194)(195)(196); from the mechanistic perspective, it was demonstrated that ACKR1 caused anti-tumor effects by interfering with CXCR2-induced STAT3 activation in pancreatic adenocarcinoma cells (192). Moreover, in prostate cancer ACKR1 expressed by vascular endothelial cells interacted with tetraspanin KAI1 (CD82) on tumor cells, leading to decreased DNA synthesis and induction of tumor cell senescence (195); in parallel, it was found that melanomaexpressed KAI interacted with endothelial cell-expressed ACKR1 preventing CXCL8-inudced gap formation in endothelial cells and leading to tumor cell senescence (197).…”
Section: Activities Of Atypical Chemokine Receptors In Cancermentioning
confidence: 99%
“…Recently, studies highlight that DARC plays a potential role in malignancy, the most essential of which is served as a inhibit barrier of metastases . Studies increasingly discovered the association between clinical outcomes and DARC: Necrosis and decreased metastases were induced by DARC in lung cancer; the absence of DARC expression in prostate cancer tended to poor survival; and the expression of DARC by epithelial ovarian cancer decreases growth potential . Multiple reports showed that downregulation of CCBP2 in transformed cells was consistent with tumor progression and oncogene activation in Kaposi sarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…Next, horseradish peroxidase-labeled goat anti-rabbit secondary antibody (Beyotime Institute of Biotechnology) was added, and the sections were incubated at 37 °C for 1 h. After in the presence of DAB reagent and counterstaining cell nuclei with hematoxylin, the sections were mounted and examined under an optical microscope. Microvessel density (MVD) was determined from five random fields (at × 200 magnification) of each section, and only tumor blood vessels with vascular lumen or linear vascular shape were used for MVD analysis [ 25 ].…”
Section: Methodsmentioning
confidence: 99%